ANALISIS MANAJEMEN STRATEGI DALAM MENGHADAPI PERSAINGAN BISNIS PADA ERAFONE METROPOLITAN MALL CILEUNGSI BOGOR - Aditya, Elza; Fadhilah, Nurul (Sekolah Tinggi Ilmu Ekonomi GICI, 2023)
The purpose of this study is to find out and analyze the influence of professionalism, the amount of competition in similar fields is certainly not easy to maintain the position of Erafone that has been attached to society. Coupled with technological advances that develop with online commerce, it becomes a challenge to retain consumers to come and visit Erafone stores. The purpose of this study is to find out and analyze what strategies are suitable for Erafone Metropolitan Mall Cileungsi Bogor. The research used is qualitative research using descriptive analysis or analysis conducted by presenting or describing data through questionnaires and interviews. With 4 respondents. The method used in this research method is QSPM (Quantitative Strategy Planning Matrix), which is a method to determine the priority of alternative strategies obtained from SWOT analysis (Strength, Weakness, Opportunity, Threat). The data analysis used is IFE Matrix analysis, EFE Matrix, IE Matrix, SWOT Matrix and QSPM Matrix. Based on the results obtained from the IFE matrix is a total score of 2.72 and the EFE Matrix of 2.85 puts Erafone Metropolitan Mall Cileungsi Bogor in the position of quadrant V is Hold and Maintan, namely by carrying out market penetration and product development.